Constituição social, interferências e contornos : o arquivo pessoal do Monsenhor João Maria Balen e o arquivo histórico Monsenhor Ruben Neis (1887-1978) - Campos, Vanessa Gomes de (2022)
The purpose of this dissertation is to analyze the overlapping relationship between the personal archive of Monsignor João Maria Balem and the place that guards it, the Arquivo Histórico Monsenhor Ruben Neis (AHMRuN) – formerly called the Arquivo Histórico da Cúria Metropolitana de Porto Alegre. Based on the outline of the outlines and the social constitution of the personal archive of Monsignor João Maria Balem (1887-1978), priest of the Archdiocese of Porto Alegre, and legacy to Monsignor Ruben Neis When he was in charge of the then Arquivo Histórico da Cúria Metropolitana, we find important elements on the constitution of the Institutional Archive itself. This is a multidisciplinary proposal, in which we use categories from the Archives alongside the historicity necessary for the topic, reinforcing the interaction between the two disciplines. From the reflection on ecclesiastical archives, we approach the AHMRuN, in order to understand how its constitution was given, as the organ of the archdiocesan structure. After knowing the place of custody of the personal archive of Balem, we go on to identify it as an archival category, in addition to its configuration, having as its northern axis the individual accumulator, the holder. When we find out about the personal archive, we notice the important relationship with the Archive that keeps it, due to the “intermediate subjectivities” (HEYMANN), that is, to the interferences in the accumulation and in the treatment given by Monsignor Ruben Neis, who allows us to highlight the “layers of interventions” (SCHWARTZ; COOK) in the process. In this sense, we understand that the AHMRuN is more than a reflection of the project of the Catholic Church (SCHEFFER), because its composition is essentially subsidiary to the performance of agents, such as Balem and Neis. Therefore, as well as the personal archive of João Maria Balem, the AHMRuN is also constituted by particular interests, associated with the worldviews and history of the active actors, especially Neis. To think about the social constitution of the archives is to reflect on the role of these agents, and, at present, with the professionalization of the place, in the methodological transparency, consciously developing a work that will attribute meaning to the materials that will be used as historical source.